Managing contacts of chlamydia: should clinics implement a test and wait process?. (January 2021) - Frackelton, Rachel; Jones, Kathy; Hamer, Beth; Jones, Sian; Hitchings, Elizabeth; Harrison, Joanne; Hughes-McGreal, Catherine; Clarke, Emily
British guidelines recommend epidemiological treatment for all chlamydia contacts during the look back period. Some UK sexual health clinics follow a test and wait process for chlamydia contacts presenting after 14 days of exposure. The aim of this retrospective service evaluation was to determine the potential impact of implementing such a process for chlamydia contacts at our clinic. We reviewed the patient records of 548 chlamydia contacts over a 1-year period, and 588 patients with chlamydia over a 5-month period. Demographic and clinical characteristics data were collected. Chlamydia prevalence was 46% (254/548) in contacts, with prevalence varying by age (p=.008) and sexual risk (p=.04), but not by time since exposure (p=.29). For patients with chlamydia, there was a mean of 1.9 days between results notification and attending for treatment; a mean of 2.2 attempts were required to contact patients to return for treatment. Chlamydia prevalence in contacts is high. Not giving empirical treatment to contacts presenting after 14 days of exposure would result in 13.1% of the cohort needing to return for treatment. Patients found to have chlamydia returned promptly once informed of positive results.